Different frequencies to estimate bone mineral content from raw bioelectrical impedance data in adolescent soccer players: a critical analysis - Cattem, Marcus Vinicius de Oliveira; Koury, Josely Correa (Frontiers in Nutrition, 2025)
IntroductionSkeletal muscle mass, body cell mass, total body water (TBW), and bone mineral mass (BMC) are components of fat-free mass (FFM), which conducts electrical energy due to its high water and electrolyte content. Multifrequency bioelectrical impedance analysis (MF-BIA) has been used to predict FFM, and studies have explored its application for quantifying BMC, a subset of FFM. However, the accuracy of the BMC predicted using MF-BIA depends on the methodological rigor of the frequency selection. This study examined the relationships between BMC and raw MF-BIA data at different frequencies.MethodsThe MF-BIA (SECA 515®) device obtained raw bioelectrical data at 5, 50, and 500 kHz. BMC was quantified using dual-energy X-ray absorptiometry (DXA). Multiple linear regression models and bioelectrical impedance vector analysis (BIVA) were applied to evaluate whole-body and segmental BMC relationships.ResultsMale adolescent soccer players (n = 149; 15.6 ± 0.6 years) participated in this study. Whole-body BMC (R2 = 0.522), and upper and lower limb BMC (R2 = 0.349) were best predicted at 5 kHz, while trunk BMC (R2 = 0.301) was best predicted at 50 kHz. BIVA revealed a leftward vector shift in participants with higher BMC quartiles. The calculated phase angle (PhA) was significantly higher in the highest BMC quartile for 5, 50, and 500 kHz in both upper and lower limbs (p < 0.05).ConclusionThese findings indicate that MF-BIA could be a supplementary tool for studying BMC in adolescent athletes. However, its utility is constrained by prediction and interpretation errors, emphasizing the importance of careful frequency selection.